High risk prenatal care: An opportunity for nutritional care - Schiavon Morgado, Mônica; Cantão dos Santos, Hully; Souza Traspadini Vial, Ludmila; do Nascimento Norete, Diésse; Moraes, Eliane; Carmo Rodrigues Barbosa, Míriam (Guará Journal, 2022)
Introduction: In order to promote adequate prenatal care, the Ministry of Health has developed manuals aimed at this sub-ject since 1986, updating them until its last edition in 2012. However, in these materials an incipient content is observed, regarding. Approach to food issues, which may limit access to such information in prenatal care services. Objectives: to verify the feeding / nutrition information contained in the prenatal materials and to characterize a high-risk prenatal care service in relation to feeding / nutrition topics. Methodology: This is a cross-sectional observational study, which, through a biblio-graphical review, verified the volume and quality of feeding/nutrition information available in prenatal materials for health professionals. In addition, the work routines and care of health professionals working in this service were observed. Result: The sample consisted of 55 pregnant women attending this high–risk prenatal care service. Conclusion: The main finding of this study revealed that the approach to food/nutrition issues was largely absent from the care provided to pregnant women.